1987
DOI: 10.1111/j.1365-3083.1987.tb02301.x
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages in T and B Cell Compartments and Other Tissue Macrophages Recognized by Monoclonal Antibody MOMA‐2

Abstract: A new monoclonal antibody, MOMA-2, is described, which recognizes monocytes and macrophages in the mouse. The antibody reacts with the majority of mononuclear phagocytes in various tissues as determined by immunohistochemistry. It differs from other macrophage markers that have been described by the strong reaction with macrophages in the lymphoid organs such as the tingible body macrophages and macrophages in T cell-dependent areas. The antibody recognizes predominantly a cytoplasmic component, although a mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(86 citation statements)
references
References 16 publications
3
82
0
Order By: Relevance
“…These cells may be monocytes/macrophages or their precursors. 32 FACS analysis also revealed decreased proportions of CD4, CD8 and CD19 cells and increased levels of NK-1.1 cells in the spleens of nontreated tumor-bearing animals. However, the total number of all splenocytes subpopulation was increased because of splenomegaly.…”
Section: Discussionmentioning
confidence: 90%
“…These cells may be monocytes/macrophages or their precursors. 32 FACS analysis also revealed decreased proportions of CD4, CD8 and CD19 cells and increased levels of NK-1.1 cells in the spleens of nontreated tumor-bearing animals. However, the total number of all splenocytes subpopulation was increased because of splenomegaly.…”
Section: Discussionmentioning
confidence: 90%
“…To identify the source of the p43, we compared the localization of p43 with those of the macrophages and endothelial cells recruited to the granulation tissue. This examination, revealed that p43 was co-localized with the MOMA2-positive cells 13 that are known to be macrophages ( Figure 1C), but not with the endothelial cells (Supplementary Figure 1 at http://ajp.amjpathol.org). To determine whether the recruited macrophages are responsible for the secretion of p43, we checked the secretion of p43 from macrophages in response to TNF-␣, which is elevated on wounding.…”
Section: Enrichment Of P43 At Wound Sitementioning
confidence: 99%
“…We obtained the wound fluids by washing the skin wound regions with PBS at the indicated times, precipitating the proteins with 10% TCA, and separating them by SDS-PAGE for Western blotting. C: The isolated granulation regions were reacted with anti-p43 and anti-MOMA2 antibodies 13 at the indicated times after wounding to visualize p43 and macrophages, respectively. The p43 and macrophages were then stained with FITC-and TRITC-conjugated secondary antibodies, respectively.…”
Section: Erk Mediates P43-dependent Proliferation Of Fibroblastsmentioning
confidence: 99%
“…Immunocytochemistry. Serial cryosections 5 m thick from the proximal aortic were fixed in acetone and incubated with monoclonal rat antibody to mouse macrophages, MOMA-2 (Accurate Chemicals) (26), or a rabbit antiserum to mouse apoE (Biodesign International, Kennebunkport, ME) diluted in PBS 1:30 and 1:300, respectively. The sections were incubated with biotinylated goat antibodies to rat (or rabbit) IgG (PharMingen) in a dilution of 1:200.…”
Section: Methodsmentioning
confidence: 99%
“…A 100-l aliquot of mouse serum was injected onto the column and separated with a buffer containing 0.15 M NaCl, 0.01 M Na 2 HPO 4 , 0.1 mM EDTA, pH 7.5, at a flow rate of 0.5 ml/min. Fifty fractions of 0.5 ml each were collected, with the lipoproteins being contained within tubes [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Protein Electrophoresis and Western Blots. The lipoproteins were extensively dialyzed in 0.15 M NaCl, 0.01 mM EDTA, at 4ЊC, and then either concentrated using Centricon filters (Amicon) and used for agarose gel electrophoresis, or precipitated using a 50-mg/ml solution of fumed silica (Cab-O-Sil; Sigma) and used for SDS/PAGE.…”
Section: Methodsmentioning
confidence: 99%